The Development of Community Participation Management by Appreciation Influence Control in Ban Den Municipality School, Mae Ai District, Chiang Mai Province - บุญทวี, ธนวัฒน์; อริยา, สมบูรณ์; เวชชะ, ประเวศ (Community and Social Development Journal, 2018)
The purposes of this study, aimed to investigate the present situations and on-going strategies for the community participation management by appreciation influence control in Ban Den Municipality School, Mae Ai District, Chiang Mai Province. Target group for the study of the community participation management included 40 members from the basic educational committee, community representatives and parent representatives, with a questionnaire survey. Another the target group for the finding community participation using appreciation influence control included 22 members from the basic educational committee, community representatives and parent representatives with a manual of the appreciation influence control technique (AIC). Qualitative Analysis were applied with the use of mean and standard deviation. Narrative technique was employed in content analysis. The findings of the study divided into two major aspects were as follows: 1. Community participation in organizational administration at glance 1.1 Academic management: Overall it was stated that the three targeted groups’ community participation in their academic management was rated at a high level. The basic educational committee and community representatives rated it at a high level, meanwhile the parent representatives rated their participation at a moderate level; 1.2 Budget management: it was stated that the three targeted groups’ community participation in their budget management was rated at a high level. The basic educational committee and community representatives rated their participation at a high level, whereas parent representatives rated their participation at a moderate level; 1.3 Personnel management: it was stated that the three targeted groups’ community participation in their personnel management was rated at a moderate level. The basic educational committee and community representatives rated their participation at a high level whereas parent representatives rated their participation at a moderate level; 1.4 General management: it was stated that the three targeted groups’ community participation in their general management was rated at a high level. The basic educational committee rated their participation at the highest level, followed by the community representatives and the student parents respectively. 2. The on-going strategies for the development of the three targeted groups’ community participation in their organizational management were suggested that the provisions for the enhancement of the school’s practical vision and missions with well-planned organizational management; the community residents’, teachers’ and student parents’ better understandings of their educational management; the community residents’ opportunities in participating in their organizational management, and the community residents’ goals for participating in their organizational management taken place in the academic year 2016 be all required. Not only should the school’s on-going strategies for participatory process development be set up, but also the school staff’s better understandings of their participation in personnel management should also be encouraged. Moreover, the other involved participants’ cooperation in effectively managing the five major projects (e.g. project for school staff’s community participation; project for community paradigm shifts on participatory educational management; project for Mother’s day with her educational sponsorship; project for Father’s day with his financial supports, and project for educational fieldtrips) should be enhanced. The information from the study help the parents, the community leaders, the school boards know the importance and adapt that the community role on the participation in the education can support and solve the education problem for the betterment of the community.